Peran Dinas Sosial melalui Program Keluarga Harapan Komponen Kesejahteraan Disabilitas dalam Penanggulangan Kemiskinan di Kota Bengkulu - Gloria Erysa Meilinda Situmorang; Amy Yayuk Sri Rahayu (Syntax Corporation, 2023)
This study aims to find out the role of the Social Departement through the disability welfare component of the Family Hope Program (PKH) in alleviating poverty in Bengkulu based on the role theory of Jim Ife and Frank Tesoriero which includes four main roles. facilitative role, educational role, representative role, and technical role. The research method used in this research is qualitative, with a descriptive approach. Data collection techniques were carried out by means of interviews, literature studies, and documentation. The technique of determining informants with purposive sampling technique. The findings of this study demonstrate that the Bengkulu City Social Department, in its capacity as an organization tasked with addressing poverty in Bengkulu, has effectively fulfilled its responsibilities in executing the program through facilitation, education, representation, and technical expertise. The Social Department has a significant role in providing welfare for beneficiaries of the Family Hope Program (PKH) in Bengkulu, particularly in the context of disability support. The PKH program demonstrates efficacy in its objective of poverty reduction and enhancement of human well-being in Bengkulu City. This study aims to explore the availability of services specifically designed to support those facing extreme poverty, with a particular focus on those who are beneficiaries of the disability component. The efficacy of this program is contingent upon not only its provision of financial aid, but also the multifarious involvement of the Social Department in fostering comprehensive well-being for these households.